Short Communication: Abundance and diversity of plant parasitic nematodes associated with BP 308 and BP 42 clones of robusta coffee in Java, Indonesia - MUTALA’LIAH MUTALA’LIAH; SIWI INDARTI; NUGROHO SUSETYA PUTRA (Biodiversitas Journal of Biological Diversity, 2018)
Mutala’liah, Indarti S, Putra NS. 2018. Abundance and diversity of plant parasitic nematodes associated with BP 308 and BP 42 clones of robusta coffee in Java, Indonesia. Biodiversitas 19: xxxx. Plant parasitic nematodes are an important limiting factor in the productivity of coffee plantations. Clone resistance and soil texture influence the severity of plant infestation by parasitic nematodes. The aim of this research was to determine the diversity of plant parasitic nematodes in two clone of Robusta coffee (BP 308 and BP 42) on soils with different contents of sand. The research was carried out in Malangsari Field (East Java), Getas Field (Central Java) and Candiroto Field (Central Java). Nematodes were extracted from soil samples by the decanting method using a whitehead tray, while roots sample by the funnel spray method with a ‘mistifier’. Differences in diversity of nematode genera between clone and location combinations were analyzed by ANOVA. The results showed that there were five genera associated with Robusta coffee, i.e. Pratylenchus, Helicotylenchus, Radopholus, Rotylenchulus, and Meloidogyne. With clone BP 308 at the Malangsari Field site where soil contained 31.3 % sand, Pratylenchus was the most abundant genus i.e. 6 nematodes/100 mL soil. On the same clone, BP 308, at the Getas Field site where soil contained 26.9 % sand, Meloidogyne was the most abundant i.e. 14.4 nematodes/10 g roots. With clone BP 42 at the Candiroto Field site with 25.5 % sand in the soil, Pratylenchus was highly abundant i.e. 60 nematodes/10 g roots.